Fluvial to estuarine transition in the middle Bloyd sandstone (Morrowan), northwest Arkansas - Unrein, Kevin Scott (Kansas State University, 2007)
The Morrowan middle Bloyd sandstone of northwest Arkansas records a fluvial to estuarine transition in a drowned incised valley system. Lower portions of outcrops contain fluvially deposited, planar-tabular cross-stratified sandstone with a uni-directional southwest paleoflow. Intervals with dune scale, intricately interwoven trough cross-stratification with northeastern paleoflow is attributed to strong tidal and wave influence in the outer estuary. Upwards the middle Bloyd changes into a muddy mid-estuarine interval with heterolithic bedding and a bi-directional northeast-southwest paleoflow. Overlying this interval a marine sand about one meter in thickness can be found containing bryozoan and crinoid fossils. Overlying the middle Bloyd, the marine Dye Shale member of the Bloyd Formation marks the transition to a dominantly marine setting.
Keywords: Morrowan; incised valley fill; Arkansas; estuarine; tidal; arkoma; Geology (0372)